PENGEMBANGAN MEDIA INTERAKTIF FABEL UNTUK MENINGKATKAN MINAT BACA DAN KETRAMPILAN MENULIS PESERTA DIDIK - Regianti, Adila Maulita; Nurdyansyah, Nurdyansyah (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2023)
This research is aimed at 3rd grade students of MI An-Nur Junwangi to increase reading interest and writing skills in learning Thematic Theme 1 Sub-theme 1 Indonesian Language Subject by using interactive media fables that have been created and developed by researchers without leaving the content of the material in the book. the module. The research used by researchers in this journal is the R&D (Research and Development) research method. This method is a research model that develops a product that will be made more attractive by not changing the original shape. This model is supported by the use of the ADDIE method (Analysis, Design, Production, Implementation and Evaluation). Researchers have developed interactive media to increase interest in reading and writing skills for students in each lesson. In this study, data collection was taken by conducting interviews with educators who teach in the lesson and observing how the process or conditions of students and classes during learning were supported by documentation during data collection. After getting the research data and analyzing the research, it can be said that in technical analysis, including technical descriptive analysis, namely quantitative obtained from expert advice and qualitative obtained from the results of calculating the percentage of experts who can be said to be feasible or not the product. Results The percentage of each expert is 95% Material Expert, 98% Media Expert and 100% Learning Practitioner Expert (Teacher). In addition, this study also uses the Paired T-Test analysis technique through SPSS, namely Pre-Test and Post-Test for students. The average result of the Pre-Test is 65.4 while the Post Test is 82.5. With these average results, it can be seen that there is a significant increase of 17. So that the product that has been developed is acceptable and feasible to be developed at MI School Institutions